Empirical Research on Seasoned Equity Offerings, Board Member Characteristics, and Corporate Investment Efficiency - Dapeng Zhu; Yongli Li (Discrete Dynamics in Nature and Society)
Seasoned equity offerings (SEO) are an important approach for listed companies to obtain funds after an initial public offering (IPO), which plays a major role in enterprises’ demand for funds. However, due to agency conflicts, information asymmetry, tunneling by major shareholders, and other behaviors, listed companies sometimes fail to make proper use of the refinancing funds. In this study, the impact of SEO on corporate investment efficiency is tested. Furthermore, the impact of board member characteristics on investment efficiency of refinancing companies is tested. Refinancing listed companies in Shenzhen and Shanghai Exchange Stock from 2009 to 2020 form the research samples. The research shows that SEO reduces the corporate investment efficiency. According to the impact analysis of the board member characteristics on the investment efficiency of refinancing companies, age heterogeneity of the board inhibits investment efficiency. The older the mean age of directors, the higher the investment efficiency. Furthermore, sex heterogeneity also inhibits investment efficiency. The more female directors, the lower the investment efficiency. Moreover, overseas backgrounds and experiences of directors also inhibit investment efficiency. These findings not only extend the research on the consequences of SEO in China, but also provide reference points and guidance for listed companies to adopt a scientific and reasonable refinancing method, give full play to the advantages, and overcome disadvantages of board members.